CREATIVE FATHERHOOD BEHIND BARS: THE READ TO YOUR CHILD PROGRAM - Tabitha Stickel; Anna Kaiper-Marquez; Esther Prins (Universidade Federal da Paraíba, 2020)
More than one-half of incarcerated people in the USA are parents of minor children. Family literacy and read-aloud programs not only provide these parents with ways to connect and communicate with their children, but also encourage children's learning and literacy development through creative means. Research on such programs, however, is scarce. This article presents an analysis of one such family literacy program operating in a rural Pennsylvania prison. Using qualitative data, the authors describe the Read to Your Child/Grandchild (RYCG) program and the experiences of the 11 fathers who participated in the program in fall 2018. The article examines how the program bridges gaps between fathers and children in communication, physical presence, and literacy development; the unique benefits the program's components afford its participants; and the fathers' acts of creativity and creation while in a restricted carceral setting.